Multiplexed bioluminescence-mediated tracking of DNA double-strand break repairs in vitro and in vivo - Chien, Jasper Che-Yung; Badr, Christian E.; Lai, Charles Pin-Kuang (Nature protocols, 2021)
The dynamics of DNA double-strand break (DSB) repairs including homology-directed repair and nonhomologous end joining play an important role in diseases and therapies. However, investigating DSB repair is typically a low-throughput and cross-sectional process, requiring disruption of cells and organisms for subsequent nuclease-, sequencing- or reporter-based assays. In this protocol, we provide instructions for establishing a bioluminescent repair reporter system using engineered Gaussia and Vargula luciferases for noninvasive tracking of homology-directed repair and nonhomologous end joining, respectively, induced by SceI meganuclease, SpCas9 or SpCas9 D10A nickase-mediated editing. We also describe complementation with orthogonal DSB repair assays and omics analyses to validate the reporter readouts. The bioluminescent repair reporter system provides longitudinal and rapid readout (~seconds per sample) to accurately and efficiently measure the efficacy of genome-editing tools and small-molecule modulators on DSB repair. This protocol takes ~2–4 weeks to establish, and as little as 2 h to complete the assay. The entire bioluminescent repair reporter procedure can be performed by one person with standard molecular biology expertise and equipment. However, orthogonal DNA repair assays would require a specialized facility that performs Sanger sequencing or next-generation sequencing. This protocol sets up a bioluminescent repair reporter system using engineered Gaussia and Vargula luciferases for noninvasive tracking of homology-directed repair and nonhomologous end joining, respectively, induced by SceI meganuclease, SpCas9 or SpCas9 D10A nickase-mediated editing.